MIDCAB Versus Off-Pump CABG: A Comparative Study - Muhammad Arsalan Ali, Muhammad Ahmed, Hamad Ali Shah (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Treatment for coronary artery disease (CAD) includes medical therapy, percutaneous coronary intervention (PCI) and coronary artery bypass grafting. Objectives: The main objective of the study is to find the comparison of MIDCAB vs open off-pump procedure CABG for single vessel coronary disease. Material and methods: This comparative analysis was conducted at Rawalpindi Institute of Cardiology, Armed Forces Institute of Cardiology, Rawalpindi and Shifa International Hospital, Islamabad from October 2019 to 2021. Informed consent was taken from all the patients before collecting the data. Patients in the MIDCAB group received sub-station hybridization to treat the diseased vessels except the left anterior descending (LAD). Patients in the OPCAB group were placed in the supine position, and combined intravenous inhalational anaesthesia was given; then, single-lumen endotracheal intubation was performed through the median incision. Results: The data were collected from 100 coronary artery disease patients. The mean age of the study patients was 54.4±10.6 years. Cigarette smoking was much more common in men than in women (32.6% vs. 0, p<0.001). The serum levels of creatinine, uric acid, and cTAS were significantly higher in men than in women (0.9±0.2 vs. 0.7±0.1, 7.6±2.1 vs. 6.8±2.3, and.0.4±0.0 vs. 0.3±0.1, respectively; p<0.001). Conclusion: It is concluded that MIDCAB procedures can be performed with similar safety as OPCAB procedures. Postoperative outcomes in terms of mortality were satisfactory, rendering this procedure at least as safe as the option of OPCAB. Practical implications: MIDCAB is considered to be the safe procedure and we may practically use this method. Key words: MIDCAB, OPCAB, Mortality, Coronary Artery Diseases, Procedures